International Norms and Albania after Communism System - Koti, Isidor (Mediterranean Journal of Social Sciences, 2012)
This article seeks to uncover the impact of the EU in the Albanian political transformations. Approaching the EU impact onAlbanian political reforms as a process of country’s socialization to the norms institutionalised in the European environment, this studydwells on both the external and domestic factors that determine the mechanisms of norm assertion in the domestic area. The first partspecifies the set of external conditions and the intervening domestic variables that induce a logic of consequentiality or appropriatenessin domestic change. The article proceeds to discuss the phenomena of European nannies to European neo-democracies. Finally, thestudy of the process of democratization in Albania illustrates the extreme case of a wider post-communist phenomenon: the Impact ofEU is translated into a consequential logic of using the democratic rhetoric and adopting democratic institutions, which are used andabused by political actors loaded with the legacies bequeathed to them by the ancient regime. This article suggests that Albaniandemocratisation could have a different trajectory without the presence of the EU pushing for and directing reforms. Messages in the formof the EU reports, evaluations and critiques, which determine the progress in the contractual relations between EU and Albania, havebecame the signposts of change to the extent that they are the epicentre around which achievements and future challenges are debatedand decided upon.